The Role of The Ash-Shidqi Remembrance Assembly in Improving Quality of Religious Education for Medan City Community - Rahmy Fuady Tanjung; Sandy Ariawan (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This paper discusses the role of the Ash-Shidqi remembrance assembly in the city of Medan in improving the quality of religious education for the people of Medan. This research is a field research using qualitative methods. The data collection process was carried out by the author by interviewing the chairman and management of the Ash-Shidqi remembrance assembly, while in analyzing the data the author applied several stages; compiling data, connecting data, reducing data, presenting data, and drawing conclusions. This study found that in improving the quality of religious education for the people of Medan, the As-Shidqi remembrance assembly launched three programs, as for the three programs as follows: First, an educational scholarship program for underprivileged and high achievers. Second, the program for distributing the Qur'an and books to Islamic boarding schools and tahfidz houses. Third, religious education program for the general public. The program consists of three activities; regular recitations every Sunday, tahlilan, and pre-marital education.